El impacto de las redes sociales y comunicacionales de la universidad Laica Vicente Rocafuerte de Guayaquil en la decisión de ingreso a carreras universitarias de los estudiantes de quinto y sexto año de bachillerato de colegios de Guayaquil - Idrovo Vélez, Norma Carolina (2016)
This project was conducted with the aim of identifying the level of impact of social networks of Vicente Rocafuerte Laica University in the fifth- and sixth year colleges Rita Lecumberri, Jorge Washington and Santa María Mazzarello. Underpinning concepts of social networking, community manager, brand positioning, public relations, marketing, impact of social networks in adolescents are included….